Trace moisture detection in oil filled transformer by ceramic sensor. Issue 1 (17th February 2015) - Saha, Debdulal; Sengupta, K
Abstract: This paper reports on the suitability of thin film nano porous γ-alumina sensor for sensing parts per million (ppm) moisture present in transformer oil. Transformer oil degrades slowly by weathering, causing dielectric break down voltage of the oil to fall down. For improving this break down voltage, water must be removed from the transformer oil. Flash point of the transformer oil ranges from 150°C to 200°C.When the oil is slowly heated up to 75°C water vapour comes out from oil which is detected by ceramic sensor. The sensor is prepared from organo-metallic precursor by sol-gel process. Gold coated α-alumina substrate was dipped within the alumina hydra-sol and a thin film of γ-alumina formed on the substrate. The sensor capacitance was measured as a function of ppm moisture level. The circuit produces an output voltage which is precisely related to the absolute value of the capacitance of the dielectric material. In order to improve the sensitivity, parallel electrode structure was patterned on the nano porous dielectric. The response is sufficiently linear in extremely low ppm level moisture. A prototype hygrometer was built for detection of trace moisture in transformer oil. Porous alumina can be produced at a relatively low cost and in a variety of structural configurations. Sol- gel processing of alumina allows superior control on pore morphology, phase formation, purity and product microstructure compared to the more traditional techniques like Anodic oxidation of alumina sheets, tape cast by different sizes of alumina powder etc.